Effective strength training for golf: What`s the right approach? - Newton, H. (Annual Review of Golf Coaching, 2007)
There is a time for nearly all facets of scientific resistance training. In preparation for more serious strength development, lifting light and moderate resistances a medium number of repetitions (eight to 12) makes sense. The utilization of heavier weights moved either slowly for added strength or quickly for improved power is the classic means of achieving peak performance at the right time in the competitive calendar. Golf and strength coaches, along with sport scientists, are encouraged to explore all the many facets of resistance training in order to provide today`s golfer with solid, safe, and scientific advice on how to improve their game. It must be acknowledged that any serious attempt at gaining increased strength and power for golf requires a good deal of elementary and intermediate instruction in the weight room. Gains in strength and power take no less time or effort than does perfecting the golf swing.